Environmental knowledge, perceived behavioral control, and employee green behavior in female employees of small and medium enterprises in Ensenada, Baja California - Galván-Mendoza, Oscar; González-Rosales, Virginia Margarita; Leyva-Hernández, Sandra Nelly; Arango-Ramírez, Paola Miriam; Velasco-Aulcy, Lizzette (Frontiers in Psychology, 2022)
The objective of the research was to analyze the effect of environmental knowledge and perceived behavioral control on the employee green behavior of female employees of SMEs in Ensenada, Baja California. The study is characterized by having a quantitative approach, a non-experimental, exploratory design and a transverse temporal dimension. 240 questionnaires were applied to female employees of SMEs in Ensenada, Baja California. The data collected was analyzed using structural equation modeling based on the partial least squares technique. The results empirically reflect the following: environmental knowledge has a positive and statistically significant effect on perceived behavioral control and employee green behavior. Also, it was found that the perceived behavioral control variable had a positive and statistically significant effect on the employee green behavior of female employees of SMEs in Ensenada, Baja California. Lastly, it was found that environmental knowledge predicts perceived behavioral control which in turn predicts employee green behavior.In this sense, such findings allow us to consider environmental knowledge and perceived behavioral control as predictive variables of employee green behavior.